Recherches sur les substances radioactives - Curie, Marie, 1867-1934 (Salt Lake City, UT : Project Gutenberg, 2013)
"Recherches sur les substances radioactives" by Marie Curie is a scientific publication written in the late 19th century. The work presents Curie's extensive research on radioactive substances, particularly focusing on uranium and the newly identified element radium. The text is aimed at a scholarly audience and contributes significantly to the field of radiochemistry. At the start of the work, Curie introduces her research, which began over four years prior, motivated by the intriguing discovery of uranium radiation by Henri Becquerel. She discusses the collaborative efforts with her husband, Pierre Curie, in studying radioactive properties and emphasizes the establishment of radium as a new, highly radioactive element. The early chapters outline the significance of various experiments conducted, the methodologies employed to study radioactivity, and the continual evolution of scientific understanding surrounding radioactive substances as more researchers engage with the topic following their discoveries. (This is an automatically generated summary.)
Release date is 2013-07-16
E-text prepared by Claudine Corbasson and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Radioactivity; Radioactive substances